The Sherwood simulation suite: overview and data comparisons with the Lyman-α forest at redshifts 2≤z≤5 - Bolton, James S.; Puchwein, Ewald; Sijacki, Debora; Haehnelt, Martin G.; Kim, Tae-Sun; Meiksin, Avery; Regan, John A.; Viel, Matteo (Oxford University Press, 2017)
We introduce a new set of large-scale, high-resolution hydrodynamical simulations of the intergalactic medium: the Sherwood simulation suite. These are performed in volumes of 103–1603h−3 comoving Mpc3, span almost four orders of magnitude in mass resolution with up to 17.2 billion particles, and employ a variety of physics variations including warm dark matter and galactic outflows. We undertake a detailed comparison of the simulations to high-resolution, high signal-to-noise observations of the Ly α forest over the redshift range 2 ≤ z ≤ 5. The simulations are in very good agreement with the observational data, lending further support to the paradigm that the Ly α forest is a natural consequence of the web-like distribution of matter arising in Λcold dark matter cosmological models. Only a small number of minor discrepancies remain with respect to the observational data. Saturated Ly α absorption lines with column densities NHI>1014.5cm−2 at 2 < z < 2.5 are underpredicted in the models. An uncertain correction for continuum placement bias is required to match the distribution and power spectrum of the transmitted flux, particularly at z > 4. Finally, the temperature of intergalactic gas in the simulations may be slightly too low at z = 2.7 and a flatter temperature–density relation is required at z = 2.4, consistent with the expected effects of non-equilibrium ionization during He ii reionization.